Integrating Prowriting for Students’ Writing Recount Text - Erni Yulianti (Future Science, 2024)
The purpose of the research was to investigate the application of Prowriting in students’ writing recount text. The researcher did the study to see if there were increasing points got by the students in applying Prowriting for students' writing Recount text. The research used classroom action research. There were 36 students from senior high school 1 Pangkalpinang from class X2 as the participants in the research. The data was collected from documentation and class observation with 2 cycles. The finding data showed that there was an improvement in the student's results. It was shown from pre-cycle students' results in writing recount text with an average score was 49,47. Then, the first cycle for the first meeting was 69,30. The first cycle for the second meeting was 71,98 and lastly for second cycle with average score was 77,61. The data of research obtained that Prowriting was the best program to handle the students’ error in creating recount text. Then, it helps students to have more motivation to revise their text. The writer assumes that pro-writing makes the meaningful the teaching and learning process.